(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Corruption of Textual Integrity in the Writings of Martin Luther. „The Jewish Question” and the „Final Solution” This paper aims to analyze the extent to which Lutheran writings influenced the „final solution” that has been forged by the Nazis. As the humus of interpretations flows from one extreme to another, this possible causal relationship must be analyzed with great care and balance, avoiding thesisism as much as possible. The paper will also review how the German Protestant Church related to Lutheran writings on the „Jewish question” and, especially, how they related to the philosophy of the Nazi party. We will also notice how the corruption of textual integrity will generate deprivation of liberties and affect the integrity of a people.